2016
DOI: 10.22521/edupij.2016.54.1
|View full text |Cite
|
Sign up to set email alerts
|

Asian International Students’ Perceptions of their University Experience

Abstract: Asian students make up the largest proportion of international students who study in the United States. Seeking a degree in higher education can be challenging for any student, but Asian students often encounter more obstacles to completion than many other international and domestic students. Culture, family and health concerns, and safety are some of the largest concerns that this study found among Asian students in the US. The study found that East-Asian international students had more issues than students f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…Like English language proficiency and self-doubt, identified in Perry et al (2017) research, this study demonstrated that lack of English proficiency led to self-doubt and low self-confidence, that in turn led to difficulty in expressing oneself. Also, a unique finding of the present study was that of participants not being able to express their feelings with their peers, as they did not know whom to trust.…”
Section: Discussionsupporting
confidence: 53%
“…Like English language proficiency and self-doubt, identified in Perry et al (2017) research, this study demonstrated that lack of English proficiency led to self-doubt and low self-confidence, that in turn led to difficulty in expressing oneself. Also, a unique finding of the present study was that of participants not being able to express their feelings with their peers, as they did not know whom to trust.…”
Section: Discussionsupporting
confidence: 53%
“…The prevalence of anxiety and depression among university students may be influenced by the complexity of the transition from late adolescence to young adulthood [ 6 ]. This common mental health risk has been associated with academic demands [ 7 ], social adjustment [ 8 ], and financial challenges that students may face [ 9 ]. Depression and anxiety can be effectively treated with either pharmacotherapy or psychotherapy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globalization has increased the rate of international students studying in different countries, alongside increasing competition between nations. International students have the potential to deliver economic, cultural and academic benefits to universities throughout a nation (Perry et al. , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Globalization has increased the rate of international students studying in different countries, alongside increasing competition between nations. International students have the potential to deliver economic, cultural and academic benefits to universities throughout a nation (Perry et al, 2017). Nations are therefore striving to provide the best education to their international students so that they can augment their human capital, which, in turn, will increase national labor productivity.…”
Section: Introductionmentioning
confidence: 99%